The THE DESCRIPTION AND THE IMPACT OF PLAYING ONLINE GAME ON PHARMACY STUDENTS IN SAMARINDA - Indah Hairunisa (Universitas Muhammadiyah Kalimantan Timur, 2019)
Online game is a game that can be accessed by the community using internet access. Online games are known to have a fun and addictive effect on their use. Indonesia is the 16th most online game user in the world. This study aims to provide an overview and the impact of the habit of playing online games on Pharmacy students in Samarinda. The method used in this study was using questionnaires distributed to at least 57 respondents of Pharmacy students in Samarinda. The results show that at least 80% of students have played online games with an average playing time of 1-2 hours in one day. The results of the questionnaire also showed an impact in the form of decreasing students' sensitivity to the surrounding environment and the tendency to speak harshly due to playing online games. Based on the results, it can be concluded that the habit of playing online games can reduce students' sensitivity to their environment and can encourage negative behavior, especially in verbal matters. This research can be used as a preliminary description of behavior changes towards the negative of students due to the habit of playing online games.